Production of C4+ (2s2p 3,1P) hollow states in collisions of 6-18 MeV C4+ (1s2, 1s2s 3S) mixed-state beams with gas targets - Laoutaris, A.; Madesis, I.; Benis, E. P.; Zouros, T. J. M. (HNPS Advances in Nuclear Physics, 2019)
Normalized electron yields of the formation of 2s2p 3,1P states from the metastable states 1s2s 3,1S and from the ground state 1s21S were obtained in 6-18MeV C4+ collisions with H2, He, Ne and Ar gas targets. The method of zero-degree Auger projectile spectroscopy was used to detect electrons emitted in the Auger decay C4+ (2s2p 3,1P) → C5+ (1s) + e-with high resolution. These states are of particular importance in the detailed study of fundamental excitation mechanisms, i.e. electron-nucleus excitation, electron-electron excitation and electron-electron excitation with spin exchange. Currently, the role of the above mechanisms in the production of the 2s2p 3,1P states is investigated utilizing variable 1s2s 3S metastable fraction beams as a function of collision energy and target species. Our latest results are presented.